Multiple occurrences of membranous nephropathy complicated with anti-glomerular basement membrane antibody and anti-neutrophil cytoplasm antibody double-negative crescentic formation since the COVID-19 pandemic: A case series - Shuang Yuan; Chao Li; ZhiBo Guo; Guang Yang; LiHong Zhang; Tao Wang (Journal of International Medical Research)
There has been an unusual increase in the incidence of anti-glomerular basement membrane disease, anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitis, and double-positive cases since the coronavirus disease 2019 (COVID-19) pandemic. Rare cases have been consistently reported, including anti-glomerular basement membrane antibody and ANCA double-positive crescentic glomerulonephritis after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as well as coexistent membranous nephropathy and proteinase 3 ANCA-associated crescentic glomerulonephritis following vaccination. We described both anti-phospholipase A2 receptor (PLA2R) antibody-positive and -negative membranous nephropathy superimposed on anti-glomerular basement membrane disease. Upon and beyond these findings, we herein reported three cases of biopsy-confirmed membranous nephropathy concurrent with anti-glomerular basement membrane antibody and ANCA double-negative crescentic formation, which manifested as acute kidney injury clinically. In one case, repeated renal biopsies confirmed de novo occurrence of crescents in the setting of PLA2R-associated primary membranous nephropathy immediately after SARS-CoV-2 infection. Subsequent use of anti-CD20 agents led to substantial recovery of renal function in two patients. Our report indicated that an indirect process resulting from downstream implications of this viral infection may be responsible for a plethora of unusual entities in glomerular diseases since the COVID-19 pandemic. As such, emerging insights may help decipher the complexity of these increasingly recognized yet equally detrimental clinicopathologic combinations, particularly in the post–COVID-19 era.